PM.34 Immune Thrombocytopenia in Pregnancy. (26th April 2013) - Hogan, JL; Walsh, C; Higgins, S; Murphy, K; McAuliffe, F
Abstract : Immune thrombocytopenia (ITP) is the most common cause of thrombocytopenia in the first half of pregnancy and occurs in one or two per thousand pregnancies. The management of these pregnancies is often directed at maintaining a sufficient platelet count for delivery and other labour ward procedures. A retrospective review, of pregnancies complicated by ITP, was performed to determine mode of delivery and mean platelet counts during pregnancy. Patients with ITP were identified from the maternal medicine database. Delivery demographics for these patients were obtained from the hospital's database. Platelet counts were obtained for each trimester of pregnancy for the mother and the neonate. There were 39 pregnancies, complicated by ITP, identified from 2005–2012. 15 were nulliparous and 5 of the patients had two pregnancies during the study period. The majority had a vaginal delivery (76.9%). The mean platelet count in the first trimester was 119, 200/µl (range 27, 000–365, 000/µl). In the second trimester, the mean platelet count fell to 99, 400/µl (16, 000–255, 000/µl) and to 89, 000/µl (22, 000–231, 000/µ) in the third trimester. There were 8 patients with platelet counts less than 50, 000/µl in the third trimester. The mean neonatal platelet count on day one of life was 200, 700/µl (42, 000–414, 000/µl) and 149, 500/µl (15, 000–279, 000/µl) on day four of life. There were 5 neonates with platelets less than 50, 000/µl. The patients in this study had a high vaginal delivery rate with low neonatal morbidity despite very low platelet counts in some mothers and babies.